Analysing the progress in service delivery towards achieving universal health coverage in Nigeria: a scoping review - Chinyere Okeke; Uchenna Ezenwaka; Adanma Ekenna; Chioma Onyedinma; Obinna Onwujekwe (BMC, 2023)
Abstract Background Attainment of universal health coverage (UHC) requires optimal utilization of health services. Poor coverage and inequitable access to healthcare could hinder improvement in service delivery towards UHC. The study analyzed the progress in service delivery coverage and equity in access to care within the Nigerian health systems based on the tracer indicators of the WHO framework for monitoring UHC. Methods We searched the literature in databases: PubMed, Scopus, Directory of Open Access Journals, Google Scholar, Science Direct and websites of relevant health Ministries, Agencies, and Organizations between March to December 2022. Search terms were identified in four broader themes: Service delivery coverage, equity, UHC and Nigeria. Data were collected through a review of 37 published articles (19 peer-reviewed articles and 8 grey documents). We synthesized the findings in thematic areas using the WHO framework for monitoring UHC. Results The findings show a slow improvement in service delivery coverage across the UHC tracer indicators; reproductive, maternal, newborn and child health, infectious diseases, non-communicable diseases and service capacity and access. With regards to equity in access to care across the tracer indicators, there has been a great disparity in the utilization of healthcare services among rural dwellers, lower educational level individuals and those with poor socio-economic status over 20 years. However, there was remarkable progress in the ownership and use of long-lasting insecticide-treated nets among rural and lowest-wealth quantile households than their urban counterpart. Conclusion There is poor coverage and persistent inequitable access to care among the tracer indicators for monitoring progress in service delivery. Attaining UHC requires concerted efforts and investment of more resources in service delivery to address inequitable access to care and sustainable service coverage for improved health outcomes.